Enzymes and muscle diseases - M. Plebani (PAGEPress Publications, 2001)
Skeletal muscle disorders may result in release of muscle enzymes into the circulation and give increased serum enzyme activity. A variety of enzymes routinely determined in the clinical laboratory may be elevated, but creatine kinase is the enzyme present in the highest concentration in muscle, and in every variety of muscle disease is the serum enzyme which shows the greatest incidence and degree of elevation. Aspartate aminotransferase is the enzyme associated most significantly with inflammation. A diagnostic algorithm based on the combined measurement of creatine kinase, aspartate aminotransferase and aldolase has been found to discriminate muscular distrophies from polymyositis and other myopathies. This combination of laboratory tests has diagnostic application and thus allows the clinician to better select patients who need to have a skeletal muscle biopsy as a diagnostic procedure.